Sirolimus Conversion After Heart Transplant: Risk Factors for Acute Rejection and Predictors of Renal Function Response. Issue 9 (6th August 2014) - Zuckermann, A.; Eisen, H.; See Tai, S.; Li, H.; Hahn, C.; Crespo‐Leiro, M. G.
<x xml:space="preserve">Abstract</x> In a randomized, comparative study of cardiac transplant patients with mild‐to‐moderate renal insufficiency, conversion from calcineurin inhibitors (CNIs) to sirolimus improved renal function at 1 year versus continuing CNIs, with an attendant risk of biopsy‐confirmed acute rejection (BCAR). Post hoc analyses were conducted to identify predictors of BCAR and GFR improvement associated with conversion. Patients with proteinuria >500 mg/day were excluded. Univariate and multivariate regression analyses tested 13 parameters for BCAR and six for GFR improvement. In 57 sirolimus‐treated patients, mean daily mycophenolate mofetil (MMF) dose was lower in those with versus without BCAR (1000 vs. 1420 mg; p = 0.014). Receiver operating characteristic analysis identified MMF dose ≤1000 mg/day as the optimal cutoff to predict BCAR. Multivariate analysis confirmed low MMF dose (odds ratio: 9.94; p = 0.007) and non‐white race (odds ratio: 15.3; p = 0.06) were independently associated with BCAR. GFR improvement was evaluated in intent‐to‐treat patients (n = 116). Significant interaction was detected between treatment effect and preexisting diabetes status (univariate p = 0.077; multivariate p = 0.022), indicating greater beneficial effect of sirolimus in those without preexisting diabetes. These findings suggest that sirolimus is more effective in improving GFR in patients without preexisting diabetes, and adequate MMF doses are needed for sirolimus conversion.